2020
DOI: 10.2147/rmhp.s277640
|View full text |Cite
|
Sign up to set email alerts
|

<p>High Burden of Antibiotic-Resistant Bacteria from Wastewater in Ethiopia: A Systematic Review</p>

Abstract: Background Currently, antibiotic-resistant bacteria (ARB) have become a serious global problem and considered as One Health challenge. Despite, wastewater contains a wide range of microbial pathogens and plays a significant role in the dissemination of ARB in the environment. However, it is the most overlooked in developing countries, particularly in Ethiopia. Methods Different article searching devices like PubMed, Web of Science, Scopus, and Google Scholar were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Similarly, a high proportion of Salmonella species, Shigella species, E. coli, and S. aureus were isolated from the hospital sewage of Hawassa University Referral Hospital. 11 In contrast to this study, the most predominant bacteria from the Al-Shifa hospital sewage system (Gaza) were Pseudomonas species (31.8%) followed by E. coli (21.5%), Klebsiella species (15%), and S. aureus (7.4%). 13 Some species of bacteria were not identified from all health institutions included in this study.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Similarly, a high proportion of Salmonella species, Shigella species, E. coli, and S. aureus were isolated from the hospital sewage of Hawassa University Referral Hospital. 11 In contrast to this study, the most predominant bacteria from the Al-Shifa hospital sewage system (Gaza) were Pseudomonas species (31.8%) followed by E. coli (21.5%), Klebsiella species (15%), and S. aureus (7.4%). 13 Some species of bacteria were not identified from all health institutions included in this study.…”
Section: Discussioncontrasting
confidence: 84%
“… 9 On the contrary, the predominant bacteria identified from wastewater of hospitals located in Addis Ababa were E. coli (32%), Salmonella (23%), Klebsiella pneumoniae (15%), and Enterobacter aerogenes (11%). 10 According to a systematic review conducted by Tesfahun et al, 11 all studies from different parts of Ethiopia reported pathogenic bacteria from wastes of health facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Pendekatan One Health menekankan pentingnya sistem pemantauan untuk mendeteksi dan merespons potensi risiko kesehatan lingkungan, manusia, dan hewan yang terkait dengan air limbah RPH. Hal ini mencakup pengujian berkala terhadap sumber air untuk mencari patogen dan kontaminan lainnya, serta memantau kesehatan hewan dan manusia di daerah sekitarnya (Asfaw et al, 2020). Pendekatan One Health mengadvokasi pengembangan dan penerapan kebijakan dan peraturan yang mendorong manajemen air limbah RPH yang berkelanjutan dan bertanggung jawab.…”
Section: Pendahuluanunclassified
“…Dissemination of antimicrobial resistance bacteria in the environment is a major problem in developing countries, mainly due to improper antibiotic usage, ineffective infection control program and lack of better management of hospital wastewater. In Ethiopia, rapid urbanization and industrialization with improper environmental planning often lead to the discharge of industrial and hospital sewage effluent directly to the environment [25]. The purpose of this study is thus to develop the DLLME method for determination of selected pharmaceutical trace residues in environmental wastewaters and applying it to wastewater sample analysis around the localities where the residues are contaminating the different environmental resources from selected hospitals in Addis Ababa.…”
Section: Introductionmentioning
confidence: 99%